Design and implementation of outdoor home smart farming based on raspberry pi for home assistant management - Maslan, Mohd Nazmin; Ramli, Izzat Rafaie; Md Fauadi, Muhammad Hafidz Fazli; Ayob, Mohd Erdi; Baharom, Mohamad Faizal; Ghazali, Ihwan; Tanjung, Tia (Malque Publishing, 2025)
Outdoor home smart farming, also known as urban farming, is the practice of cultivating fruits, herbs, or vegetables for personal consumption on a small scale within a residential area. It is more sustainable compared to conventional agriculture in all aspects. However, there were various challenges in implementing outdoor home smart farming, including limitation or lack of skills, resources, or infrastructure to produce good and high-quality crops. This study addresses these challenges by integrating Python scripting and Linux OS with hardware components like the Raspberry Pi 4 Model B, ESP32, soil moisture sensors, and UV lights. Home Assistant, an open-source software, was utilized to run the script programming for outdoor home smart farming. The integrated smart devices into Home Assistant were used to monitor and analyze the farming parameters outcomes to assist decision-making and provide further user action. As a result, the system was efficient due to only consuming 0.16% for water usage and 0.64% for energy consumption compared to daily household use, as well as reducing water usage by up to 82.45% for the watering process. These results highlight the system’s capability to optimize resource usage and enhance crop productivity while minimizing environmental impact. By leveraging smart devices and IoT frameworks, the study showcases how modern technology can revolutionize traditional farming practices. The automated system not only reduces manual labor but also provides real-time data to assist in decision-making and further user actions. In conclusion, the implementation of Home Assistant management based on Raspberry Pi in outdoor home smart farming effectively addresses the challenges of urban agriculture.